Entrepreneurial Passion As Mediator Of The Influence Of Entrepreneurial Self-Efficacy Toward Entrepreneurial Performance - Dewi Nurmalasari, Osly Usman, Nina Oktarina (International Journal of Advanced Science and Technology, 2020)
This study aims to study the effect of self-efficacy on self-entrepreneurship on entrepreneurial performance, with entrepreneurial passion. Considered the which is an important driving factor and is used to mediate between the two variables. Practically the results of the research can be used to encourage the spirit of entrepreneurs in developing and establishing new business activities. The technique of data analysis used in this study is to use SEM through SmartPLS version 3.0. The testing is Carried out through three stages items, namely the inner models, outer models, and hypothesis testing. The results showed that mediates the effect of entrepreneurial passion between entrepreneurial self-efficacy on entrepreneurial performance. This research is expected to be Able to Become a reference material for literature and be developed for further research. Keyword: Entrepreneurial Passion, Entrepreneurial Performance, Entrepreneurial Self-Efficacy.